1999
DOI: 10.1016/s0954-6111(99)90026-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (3-year) economic evaluation of intensive patient education for self-management during the first year in new asthmatics

Abstract: Patient education and self-management programmes have proved effective in many studies with short follow-up periods. We studied the 3-year cost-effectiveness of an intensive programme of patient education and supervision for self-management. The study consisted of 162 consecutive newly diagnosed asthmatics who were randomized either into an intervention group (IG) receiving intensive patient education and supervision for self-management at an outpatient clinic during the first year, or a control group (CG) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…This finding suggests that education programs, such as the one used in this study, can increase patient knowledge about asthma. As in several previous studies (Clark & Nothwehr, 1997;Kauppinen et al, 1999;Meszaros, Orosz, Mgyar, Mesko, & Vincze, 2003;Tousman, Zeitz, Taylor, & Bristol, 2007), the results of this study indicate that differences in asthma knowledge scores at follow-up likely reflect an effect of the educational programVthe goal of which was to enable patients to monitor, to control, and to manage their disease with the aid of an asthma workbook used through the study period. Despite intervention, the comparison group also showed an increased knowledge about asthma.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding suggests that education programs, such as the one used in this study, can increase patient knowledge about asthma. As in several previous studies (Clark & Nothwehr, 1997;Kauppinen et al, 1999;Meszaros, Orosz, Mgyar, Mesko, & Vincze, 2003;Tousman, Zeitz, Taylor, & Bristol, 2007), the results of this study indicate that differences in asthma knowledge scores at follow-up likely reflect an effect of the educational programVthe goal of which was to enable patients to monitor, to control, and to manage their disease with the aid of an asthma workbook used through the study period. Despite intervention, the comparison group also showed an increased knowledge about asthma.…”
Section: Discussionsupporting
confidence: 80%
“…Patients are also often uninformed about the effect of education on HRQOL (Gallefoss et al, 1999). In addition, Kauppinen, Sintonen, Vilkka, and Tukiainen (1999) described that patient education did not increase HRQOL in patients with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Additional long term studies are needed to confirm the findings of this cost analysis of nurseled outpatient management in patients with more severe asthma. Previous studies have evaluated the effect of educational intervention by asthma nurses on the costs of management of asthma both in children and adults [10,12,[22][23][24][25]. The economical consequences of these interventions were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The economical consequences of these interventions were inconclusive. Some of these studies reported a cost reduction [10,12,22,23], whilst others found that extra investments were needed to achieve a reduction in healthcare utilisation of the patients [24,25]. In these studies, however, the asthma nurse intervention was additional to the routine medical care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation